2020
DOI: 10.1177/1362361320916967
|View full text |Cite
|
Sign up to set email alerts
|

Types and correlates of school non-attendance in students with autism spectrum disorders

Abstract: School non-attendance in autism spectrum disorders has received very little attention to date. The study aimed to provide a comprehensive description of school non-attendance in students with autism spectrum disorders. Through an online survey, parents of 486 children (mean age: 11 years) reported on school attendance over 1 month and reasons for instances of non-attendance. On average, students missed 5 days of school of a possible 23 days. Persistent non-attendance (absent on 10%+ of available sessions) occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 34 publications
5
52
1
Order By: Relevance
“…This asks parents to report on the number of days of school missed in the last four weeks across 14 possible reasons. Through using the SNACK, Totsika et al (2020) identified that the most frequent cause of school non-attendance in students on the autism spectrum was school reluctance/refusal, accounting for 43% of absences. "Non-problematic" absences (e.g., medical appointments) were also common, accounting for 32% of all absences.…”
Section: Types Of School Non-attendancementioning
confidence: 99%
See 4 more Smart Citations
“…This asks parents to report on the number of days of school missed in the last four weeks across 14 possible reasons. Through using the SNACK, Totsika et al (2020) identified that the most frequent cause of school non-attendance in students on the autism spectrum was school reluctance/refusal, accounting for 43% of absences. "Non-problematic" absences (e.g., medical appointments) were also common, accounting for 32% of all absences.…”
Section: Types Of School Non-attendancementioning
confidence: 99%
“…Only one study to data has looked at multiple forms of school non-attendance in autism specifically. That one study (Totsika et al, 2020) plus the small number of studies focusing upon school refusal and school exclusion all highlight the importance of considering child, family, and school factors from across the KiTeS framework as predictors of school non-attendance, and of exploring the possibility of differing factors predicting different types of school non-attendance. There is therefore a clear and pressing need for research which explores a broad range of both "problematic" and "non-problematic" forms of school non-attendance and builds upon the range of child, family, and school factors identified as predictors.…”
Section: Types Of School Non-attendancementioning
confidence: 99%
See 3 more Smart Citations